Impact of patient information leaflets on pain medication intake behavior: a pilot study. (November 2017) - Schmitz, Julia; Kamping, Sandra; Wiegratz, Janine; Müller, Maike; Stork, Jan; Colloca, Luana; Flor, Herta; Klinger, Regine
Abstract: Introduction: Patient information leaflets on pain medication primarily list side effects while positive effects and action mechanisms remain underrepresented. Nocebo research has shown that negative instructions can lower analgesic effects. Objectives: Research on information leaflets and their influence on mood, memory of side effects, and intake behavior of healthy participants is needed. Methods: To determine the ratio of positive to negative phrases, 18 information leaflets of common, over-the-market analgesics were examined of which 1 was selected. In a randomized, controlled study design, 18 healthy participants read this leaflet while 18 control group participants read a matched, neutral leaflet of an electrical device. Collected data concerned the recall of positive and negative contents, mood, anxiety, and the willingness to buy and take the drug. Results: All examined leaflets listed significantly more side effects than positive effects (t17 = 5.82, P < 0.01). After reading the analgesic leaflet, participants showed a trend towards more negative mood ( F 1, 34 = 3.78, P = 0.06, ηp 2 = 0.1), a lower intention to buy [χ 2 (1, n = 36) = 12.5, P < 0.01], a higher unwillingness to take the medication [χ 2 (1, n = 36) = 7.2, P < 0.01], and even a greater recall for side effects than positive effects (t17 = 7.47, P < 0.01). Conclusion: Reading the patient information leaflets can increase fear and lower the intention to buy and the willingness to take a pain medication. Abstract : Negative wording in package information leaflets of pain medication is associated with a tendency to evoke negative emotions and lower willing to take medication.